Morbidity and Mortality in Systemic Lupus Erythematosus During a 10-Year Period - Ricard Cervera; Munther A. Khamashta; Josep Font; Gian Domenico Sebastiani; Antonio Gil; Paz Lavilla; Juan Carlos Mejía; AO. Aydintug; H Chwalińska-Sadowska; Enrique de Ramón; Antonio Fernández‐Nebro; Mauro Galeazzi; et al. (2003)
In the present study, we assessed the frequency and characteristics of the main causes of morbidity and mortality in systemic lupus erythematosus (SLE) during a 10-year period and compared the frequency of early manifestations with those that appeared later in the evolution of the disease. In 1990, we started a multicenter study of 1,000 patients from 7 European countries. All had medical histories documented and underwent medical interview and routine general physical examination when entered in the study, and all were followed prospectively by the same physicians during the ensuing 10 years (1990–2000). A total of 481 (48.1%) patients presented 1 or more episodes of arthritis at any time during the 10 years, 311 (31.1%) patients had malar rash, 279 (27.9%) active nephropathy, 194 (19.4%) neurologic involvement, 166 (16.6%) fever, 163 (16.3%) Raynaud phenomenon, 160 (16.0%) serositis (pleuritis and/or pericarditis), 134 (13.4%) thrombocytopenia, and 92 (9.2%) thrombosis. When the prevalences of the clinical manifestations during the initial 5 years of follow-up (1990–1995) were compared with those during the ensuing 5 years (1995–2000), most manifestations were found to be more frequent during the initial 5 years. Of the 1,000 patients, 360 (36%) presented infections, 169 (16.9%) hypertension, 121 (12.1%) osteoporosis, and 81 (8.1%) cytopenia due to immunosuppressive agents. Twenty-three (2.3%) patients developed malignancies; the most frequent primary localizations were the uterus and the breast. Sixty-eight (6.8%) patients died, and the most frequent causes of death were similarly divided between active SLE (26.5%), thromboses (26.5%), and infections (25%). A survival probability of 92% at 10 years was found. A lower survival probability was detected in those patients who presented at the beginning of the study with nephropathy (88% versus 94% in patients without nephropathy, p = 0.045). When the causes of death during the initial 5 years of follow-up (1990–1995) were compared with those during the ensuing 5 years (1995–2000), active SLE and infections (28.9% each) appeared to be the most common causes during the initial 5 years, while thromboses (26.1%) became the most common cause of death during the last 5 years. In conclusion, most of the SLE inflammatory manifestations appear to be less common after a long-term evolution of the disease, probably reflecting the effect of therapy as well as the progressive remission of the disease in many patients. Meanwhile, a more prominent role of thrombotic events is becoming evident, affecting both morbidity and mortality in SLE.